EVALUATION OF INTESTINAL PARASITOSIS, NUTRITIONAL STATUS AND SOCIAL INDICATORS IN STUDENTS OF FOUR ELEMENTARY PUBLIC SCHOOL OF DIVINÓPOLIS CITY, MINAS GERAIS, BRAZIL - Valadares Pereira, Valeriana (2010)
Intestinal parasites are widely distributed and recognized as Public Health problems, mainly in the third world countries, where they are endemic. In this sense, the purpose of this study was to evaluate the association between enteroparasitosis, nutritional status and social indicators in children aged 6 to 14 years old who are enrolled in public schools. Therefore, part of the study was carried out with 523 pupils. For the copropatological examinations, spontaneous sedimentation and Kato-Katz methods were used; for the nutritional assessment, the anthropometric methods, evaluated according to the program of World Health Organization: Who Anthro Plus. Only 56.90% of the population studied has sanitation, and the majority of them (67.5%) with family income of one to two minimum wages. From the parasitological diagnoses, 26.77% had abnormal tests with higher percentage for the protozoan Giardia lamblia (13.57%). The results also showed that 2.14% of the parasitized individuals who were evaluated by anthropometry, showed low stature for their age and 3.60% of them showed low Body Mass Index (BMI). In addition, the results showed that the frequencies of children with overweight and obesity were 10.70% and 6.43%. The results also showed that among the analyzed variables, the treatment of water and the characteristics of the vessel sanitary housing were significantly associated with the intestinal parasites (value-p 0.05). In this way, the results presented indicate the necessity of implantation of actions for prevention and the promotion of health of this population.